Dispensing Materials of mobile Robot cooperating with Perception Sensor Network - An, Kijin; Choi, JongSuk; Do Hoang, Minh; Park, JiGwan (2014 11TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2014)
In this paper, we present a perception sensor network (PSN) system for automatically tracking location and identification of multiple human. We propose a fusion method for seamless human tracking over multiple kinects and for tracking human name using pan-tilt-zoom camera operations. By assistant with PSN, mobile robot understands multiple human' identification and location information while robot is moving. Finally, we have tested a robot scenario of dispensing paper materials to multiple human cooperating with PSN.